Deconstructing emotional labor - Hechanova, Ma. Regina M. (Philippine Journal of Psychology, 2011)
"The study examines emotional labor in the Philippines call center industry. Surveys were administered to 507 Filipino call center agents to test the relationship of the two facets of emotional and contextual dissonance, it was hypothesized that the mechanisms underlying the two facets of emotional labor are different."